17β‐Estradiol administration promotes delayed cutaneous wound healing in 40‐week ovariectomised female mice. Issue 5 (6th August 2014) - Mukai, Kanae; Nakajima, Yukari; Urai, Tamae; Komatsu, Emi; Nasruddin,; Sugama, Junko; Nakatani, Toshio
Abstract: This study investigated the effect of 17β‐estradiol on wound healing in 40‐week ovariectomised female mice. Thirty‐six‐week‐old female mice were divided into three groups: medication with 17β‐estradiol after ovariectomy (OVX + 17β‐estradiol), ovariectomy (OVX) and sham (SHAM). The mice received two full‐thickness wounds, and the OVX + 17β‐estradiol group was administered 17β‐estradiol at 0·01 g/day until healing. In the OVX + 17β‐estradiol group, the ratio of wound area was significantly smaller than those of the OVX and SHAM groups on days 1–3, 5, 6, 8–12 and 9–12, respectively, the numbers of neutrophils and macrophages were significantly smaller than those on days 3 and 7, the ratio of re‐epithelialisation was significantly higher than those on days 3 and 11, the ratio of myofibroblasts was significantly higher than those on day 11 and smaller on day 14, and the ratio of collagen fibres was significantly larger than that of the OVX group on days 7–14. We found that 17β‐estradiol administration promotes cutaneous wound healing in 40‐week female mice by reducing wound area, shortening inflammatory response, and promoting re‐epithelialisation, collagen deposition and wound contraction. Our results suggest that cutaneous wound healing that is delayed because of ageing is promoted by exogenous and continuous 17β‐estradiol administration.